G454(P) Flagellate erythema associated with juvenile dermatomyositis. (12th March 2018) - Hew, CH; Solman, LS; Taylor, GT; Clark, SC; Amin, TA; Wood, MW
Abstract : Aim: Flagellate erythema was first reported in association with bleomycin treatment and since then has been linked to chemotherapeutic agents, dermatomyositis, adult-onset Still disease and Shiitake mushroom dermatitis. To date, only one patient with juvenile dermatomyositis and flagellate erythema has been reported in the literature. Hence, we would like to present this case and highlight importance of this uncommon dermatological condition in children. Method: A 9-year-old girl presented in 2016, with a 2 month history of new onset proximal muscle weakness, heliotrope rash, Gottron's papules, leg erythema and soft tissue restriction at elbows, hips and knees. Muscle biopsy and MRI confirmed myositis and fasciitis. Juvenile dermatomyositis was diagnosed. She commenced steroid therapy, initially intermittent monthly pulsed intravenous methylprednisolone, with oral prednisolone, in conjunction with subcutaneous methotrexate and oral hydroxychloroquine. Two months later, due to lack of significant improvement and deterioration in muscle function, intermittent pulsed intravenous cyclophosphamide was substituted for methotrexate, with improvement in muscle weakness. Three months into cyclophosphamide therapy, she developed a florid, widespread eruption, with violaceous, urticated erythema of the face and upper trunk with areas of sparing. There were also erythematous, linear flagellate areas on her proximal limbs and back. Dermatographism was absent. There was no associated deterioration in muscle strength or elevation of inflammatory markers or muscle enzymes at that time. No relation to medication or potential allergic exposures was noted. Intravenous immunoglobulin therapy was commenced but unfortunately caused an anaphylactic reaction. Methotrexate was restarted and she has been maintained since on a combination of this with hydroxychloroquine, sun protection, topical steroids and calcineurin inhibitors with improvement in her skin and muscle strength and oedema on MRI. Result: Skin biopsy showed a marked vacuolar interface reaction with colloid bodies and epidermal atrophy associated with a mild perivascular lymphocytic infiltrate in the superficial dermis with absence of eosinophils and increased dermal oedema and mucin. The features were in keeping with a flagellate erythema secondary to dermatomyositis. Conclusion: The pathogenesis is not completely clear, although physical injury, sun exposure or minor trauma could be incriminated. The significance of this rash in relation to the prognosis or underlying neoplasm in adults remains unclear.